2017
DOI: 10.1155/2017/4139439
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Gemigliptin, a Dipeptidyl Peptidase-4 Inhibitor, against Cisplatin-Induced Nephrotoxicity in Mice

Abstract: Dipeptidyl peptidase-4 (DPP-4) inhibitors are widely used antihyperglycemic agents for the treatment of type 2 diabetes mellitus. Recently, the pleiotropic actions of DPP-4 inhibitors have drawn much attention. In the present study, we aimed to examine whether gemigliptin, a recently developed DPP-4 inhibitor, could protect against cisplatin-induced nephrotoxicity. We showed that pretreatment with gemigliptin attenuated cisplatin-induced renal dysfunction, as shown by analysis of plasma creatinine levels and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Images were captured using the NIKON A1+ confocal microscope (Nikon, Tokyo, Japan). Tubular damage in PAS-stained kidney sections was scored at a ×200 magnification using 10 randomly selected fields for each kidney according to the level of cortical tubular injury, as previously described: 0, normal; 1, 1–10%; 2, 11–25%; 3, 26–45%; 4, 46–75%; and 5, 76–100% [10].…”
Section: Methodsmentioning
confidence: 99%
“…Images were captured using the NIKON A1+ confocal microscope (Nikon, Tokyo, Japan). Tubular damage in PAS-stained kidney sections was scored at a ×200 magnification using 10 randomly selected fields for each kidney according to the level of cortical tubular injury, as previously described: 0, normal; 1, 1–10%; 2, 11–25%; 3, 26–45%; 4, 46–75%; and 5, 76–100% [10].…”
Section: Methodsmentioning
confidence: 99%
“…Cisplatin (cis-dichlorodiammine platinum II) is a platinum compound and antineoplastic drug, with broad-spectrum activity against various solid cancers [ 1 , 2 ]. The anticancer activity of cisplatin increases in accordance with dose augmentation, but increased cisplatin doses cause severe side effects [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been argued whether DPP‐IV must be or must not be administered to cancer patients with diabetes, whereas other studies support the oral administration of DPP‐IV inhibitors in order to either enhance tumor immunotherapy or to slow the growth of different tumors or to suppress colorectal cancer lung metastases in mice . Other studies have demonstrated their therapeutic effects on obesity, neuropathy, and hepatic and renal pathologies. Recent studies have also shown that it is possible to design DPP‐IV inhibitors with dual bioactivity on other targets involved in cardiovascular diseases like ACE or β‐adrenergic receptors …”
Section: Introductionmentioning
confidence: 99%